2019
DOI: 10.1177/0003319719848547
|View full text |Cite
|
Sign up to set email alerts
|

Use of PRECISE-DAPT Score and Admission Platelet Count to Predict Mortality Risk in Patients With Acute Coronary Syndrome

Abstract: The PREdicting bleeding Complications In patients undergoing Stent implantation and subsEquent Dual Antiplatelet Therapy (PRECISE-DAPT) score has been validated to predict bleeding complications in patients undergoing stent implantation and dual antiplatelet therapy. This score does not include the platelet count (PC), which has been shown to be an independent marker of mortality in patients with acute coronary syndrome (ACS). We assessed the role of the PRECISE-DAPT score calculated on admission for mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…A study by Morici used P-DAPT score and platelet count on admission and found that the score ≥ 25 to be an independent predictor of mortality in patients with ACS undergoing PCI. 20 However, this study lacks data on AF patients. Iwasaki reported an association of P-DAPT score ≥ 25 with major adverse cardiac events (MACE) in patients with AF undergoing PCI.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A study by Morici used P-DAPT score and platelet count on admission and found that the score ≥ 25 to be an independent predictor of mortality in patients with ACS undergoing PCI. 20 However, this study lacks data on AF patients. Iwasaki reported an association of P-DAPT score ≥ 25 with major adverse cardiac events (MACE) in patients with AF undergoing PCI.…”
Section: Discussionmentioning
confidence: 97%
“…In the past, various efforts have been made to predict mortality in patients undergoing PCI. A study by Morici used P‐DAPT score and platelet count on admission and found that the score ≥ 25 to be an independent predictor of mortality in patients with ACS undergoing PCI 20 . However, this study lacks data on AF patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, there was not a robust, interoperable, and universal risk score that could be extended to different populations, which is mainly caused by prediction algorithms derived from different cohorts and a complex and time-varying clinical process ( 8 11 ). Meanwhile, previous studies demonstrate that an additive value of one risk score combined with a biomarker, angiographic characteristic, and with another risk score to risk predicting ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Thrombocytopenia has been associated with bleeding events and increased mortality, whereas thrombocytosis has been associated with increased thrombotic events and overall mortality. [4][5][6]13,20 Two prior observational studies 22,23 have explored the significance of the CBC as a whole, assessed either during baseline hospitalization 22 or upon hospital admission, 23 in patients with CAD (both stable and unstable) and found it to be a better predictor of an increased risk for all-cause mortality and MACE, compared to traditional stratification tools.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Accordingly, Hb levels, white blood cell (WBC), and platelet count (PC) have been separately associated with worse prognosis in patients with ACS, and all of these parameters have been included in postdischarge stratification tools in this setting. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] However, no study has specifically explored the role of WBC count, Hb, and PC parameters, grouped together as single predictor, and taken on admission (WBC) and at discharge (Hb, PC), respectively, on ischemic and bleeding events in the patients with ACS.…”
Section: Introductionmentioning
confidence: 99%